Pengaruh Pemasaran Internal dan Kepuasan Kerja Terhadap Kinerja RSI Ibnu Sina Yarsi Sumbar Menurut Persepsi Karyawan Tahun 2020 - Meri Herliza Herman; Yulia Hendri Yeni (Jurnal Admmirasi, 2021)
Background: : Internal marketing in hospital is important in explaining employee perceptions of organizational performance and quality. The purpose of this study was to analyze the effect of internal marketing and employee satisfaction on the performance of the Islamic Hospital Ibnu Sina. Methode: This research is a quantitative descriptive study with data collection techniques in the form of distributing questionnaires to research subjects. After collecting the data, the data is processed using Sem smartPls3.0, and interpreting the results of the analysis, so that the necessary conclusions can be drawn in answering the problem formulation. Result: Internal marketing and job satisfaction have a significant effect on organizational performance. Conclusion: Internal marketing has been implemented quite well in RSI Ibnu Sina and there is an effect of internal marketing on organizational performance through employee job satisfaction as an intervening variable. Keywords : Internal Marketing, Employee, Satisfaction, Performance.